Studies on Monobutyltin(IV) Derivatives of 3-Hydroxy-2-naphthoic Acid - Mittal, Pankaj; Kumar Pachouri, Manoj; Sharma, R.C. (Asian Journal of Chemistry, 2010)
Some new monobutyltin(IV) derivatives of 3-hydroxy-2-naphthoic acid in different molar ratios, viz., 1 : 1, 1 : 2, 1 : 3 and 2 : 1 have been synthesized. The synthesized derivatives have been characterized by elemental analyses, IR, spectral data, PMR spectral data and molar conductance measurements. The products were screened for pesticidal activities against the pest called Etribolium castaneum (red flour beetle). The monobutyltin(IV) derivatives exhibited enhanced pesticidal effect as compared to the ligand fragments alone.